The house of Dies Drear - Hamilton, Virginia (New York, NY : Simon Pulse, 1984)
A black family tries to unravel the secrets of their new home which was once a stop on the Underground Railroad.
Originally published: New York : Macmillan, 1968.
Keywords: Children's stories, American; Detective and mystery stories, American; African Americans -- Juvenile fiction; Underground Railroad -- Ohio -- Juvenile fiction; African Americans -- Fiction; Underground Railroad -- Fiction; Ohio -- Juvenile fiction; Ohio -- Fiction; Mystery fiction